Effects of Chronic Stress and Comfort Food in Testicular Morphology in Adult Wistar Rats - Carina F. Barnabé; Roger G. Marchon; Maria V. C. Pinto; Bianca M. Gregório; Anneliese Fortuna-Costa; Francisco J. B. Sampaio; Diogo B. De Souza (International Brazilian Journal of Urology)
ABSTRACT Purpose: To investigate the effect of chronic stress on testicular morphology in adult Wistar rats, as well as the impact of comfort food consumption on these parameters. Material and methods: 32 Wistar rats (10 weeks old) were divided into four groups: control (C), stressed (S), control + comfort food (C+CF), and stressed + comfort food (S+CF). Chronic stress was induced by the restraint method during 8 weeks in groups S and S+CF, while groups C and C+CF were maintained under normal conditions. Groups C and S received a standard rat chow diet, while groups C+CF and S+CF received both the standard chow and comfort food (Froot Loops®). After 8 weeks of experiment, all animals were euthanized and the testes were collected for histomorphometric, immunohistochemical and gene expression analysis. Results: Comfort food was preferred over standard chow in groups C+CF and S+CF, but this preference was more preeminent in stressed animals (S+CF). The consumption of comfort food resulted in testicular weight reduction. The seminipherous epithelium was reduced in group S in comparison to controls. While comfort food also reduced the epithelium in C+CF in comparison to controls, for group S+CF the comfort food ameliorated the stress-induced damage. The cell proliferation rate and the relative expression of StAR and BLC2 genes were similar between the groups. Conclusion: Both chronic stress and comfort food consumption resulted in morphological alterations of the testes but the consumption of comfort foods during chronic stress partially prevented the stress-induced detrimental effects on testes.